Nyai yang Menghidupkan dan Kiai yang Dikenang: Invisibilitas Perempuan dalam Narasi Pesantren - Nadiatul Maziyyah Attarwiyah; Ahmad Barizi; Roibin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The phenomenon of Nyai in pesantren life reveals a paradox between their substantial contributions and their lack of narrative recognition. Nyai often serve as the center of caregiving, moral education, female student development, management of women’s relations, and the emotional support system of the pesantren. However, public narratives of pesantren more frequently position the kiai as the primary figure, the owner of history, and the symbol of institutional authority. Previous studies on pesantren have extensively discussed the kiai as the central figure, yet only limited research has specifically examined how the contributions of Nyai become invisible within pesantren narratives. This article aims to analyze the invisibility of Nyai by employing Pierre Bourdieu’s theory of symbolic capital and Nancy Fraser’s theory of recognition. This study uses a qualitative method with a socio-critical approach. Data were collected through observation, interviews, and analysis of pesantren institutional narratives. The findings show that: (1) there is a separation between the labor of pesantren life and the symbolic ownership of pesantren narratives, in which Nyai sustain the daily life of the pesantren while kiai dominate as the owners of symbolic narratives; (2) the authority of Nyai experiences a gendered conversion failure, namely the failure of Nyai’s social, cultural, religious, and affective capital to be converted into public authority; and (3) the invisibility of Nyai occurs through partial recognition, where Nyai are respected as caregivers and moral figures but are not yet fully acknowledged as central subjects in pesantren history. Academically, this article contributes by offering a new analytical framework for understanding narrative injustice in women’s religious authority within pesantren. Institutionally, this article encourages pesantren to develop more equitable historical documentation, media representation, and formal recognition of Nyai’s contributions.